Slant Angle and Its Influence on Rock Cutting Performance. (13th June 2018) - Sun, Yong; Li, Xingsheng
Abstract : Rock cutting is an important aspect of the civil engineering, for example, tunnelling. To improve cutting efficiency, it is important to understand the rock failure (fracture) mechanisms and the influences of cutting parameters on rock fracture behaviour. This study identified that the relative position of a pick (rock cutting tool) to the rock surface is critical to the cutting performance of the pick during rock cutting process. However, the pick tilt angle commonly used by the industries is not sufficient to describe this relative position. To address this issue, a new angle named "slant angle" is introduced. The slant angle of a pick is determined by its tilt angle and the inclination angle of the rock surface. The calculation of the slant angle is presented. A series of laboratory rock cutting experiments were conducted to investigate the influence of the slant angle on cutting force and rock fracture pattern, and two new findings were made: (1) the rotational angle of the groove cut by a tilted pick was possibly different from the tilt angle and (2) all forces on a pick increased significantly with the increase of the slant angle. The findings of this study can help improve the rock cutting efficiency.